Dwr a Phwer yn Nyffryn Camwy: heriau a gwrthdaro ynghylch sefydlu a rheoli system ddyfrhau - Williams, Fernando (2023)
The aim of this article is to construct the history of the irrigation system in the Lower Chubut Valley created by the Welsh settlers that arrived in Patagonia (Argentina) in 1865, which complicated the relationship that existed between this infrastructure and the ever-changing sociopolitical framework. This will involve focusing on the institutions that the Welsh settlers themselves established and the conflicts that arose between them and the Argentine state, which took over the administration of irrigation in 1943. Emphasis will be given to the agency of water within the process that led to reinforcing and growing the irrigation infrastructure, and attention will also be given to the symbolic dimension of the objects that constitute this infrastructure, thereby enabling a reflection on their changing meanings.